Legal study on the combat of trafficking in women for the purpose of forced prostitution in Slovakia : country report - Burčiková, Petra; Kollárová, Henrieta; Kružliaková, Tatiana (Vienna: BIM, 1999)
"Written by Petra Burčiková, Henrieta Kollárová and Tatiana Kružliaková ; funded by the Constitutional & Legislative Policy Institute/OSI ; published by the Ludwig Boltzmann Institute of Human Rights"